Dynamic Changes and Prognostic Value of Gut Microbiota-Dependent Trimethylamine-N-Oxide in Acute Ischemic Stroke - Tan, Chuhong; Wang, Huidi; Gao, Xuxuan; Xu, Ruoting; Zeng, Xiuli; Cui, Ziming; Zhu, Jiajia; Wu, Qiheng; Xia, Genghong; Zhou, Hongwei; He, Yan; Yin, Jia (Frontiers in Neurology, 2020)
Background: Acute ischemic stroke (AIS) is an atherothrombotic disease. Trimethylamine-N-oxide (TMAO), a gut microbiota-dependent metabolite, has been shown to be proatherogenic and prothrombotic. However, the involvement of TMAO in AIS remains unclear. This study aimed to observe the dynamic changes of TMAO in AIS patients and identify the prognostic value of TMAO for major ischemic events and unfavorable functional outcomes. Methods: This study included 204 AIS patients and 108 healthy controls. Blood samples for TMAO analyses were drawn at admission, 2 days and 7 days of admission. Logistic regression models and receiver operating characteristic curves were established to identify associations between TMAO levels and major ischemic events (ischemic stroke, myocardial infarction or death from an ischemic vascular event), as well as unfavorable functional outcomes (modified Rankin Scale score ≥3), at 90 days and 12 months. Results: TMAO levels showed no significant changes before and within 24 hours of AIS treatment (at admission) but decreased significantly thereafter. Elevated log2-transformed baseline TMAO levels were associated with increased risks of 90-day (odds ratio [OR], 2.62; 95% confidence interval [CI], 1.55-4.45; p<0.001) and 12-month (OR, 3.59; 95% CI, 2.12-6.09; p<0.001) major ischemic events, as well as 90-day (OR, 2.89; 95% CI, 1.46-5.71; p=0.002) and 12-month (OR, 2.58; 95% CI, 1.50-4.46; p=0.001) unfavorable functional outcomes, after adjustments for confounding factors. The areas under curve of baseline TMAO levels for predicting 90-day and 12-month major ischemic events were 0.72 (95% CI, 0.61-0.83; p<0.001) and 0.76 (95% CI, 0.66-0.85; p<0.001). Baseline TMAO levels improved the prognostic accuracy of conventional risk factors, National Institutes of Health Stroke Scale (NIHSS) score and N-terminal B-type natriuretic peptide (NT-proBNP) level. Conclusions: TMAO levels decreased with time since stroke onset. Elevated TMAO levels at an earlier period portended poor stroke outcomes, broadening the potential clinical utility of TMAO as an independent prognostic marker and therapeutic target.